Management of adnexal tumor - Valdivieso, Roger (2015)
This is a retrospective study that evaluates de associated risk)actors for ovarian malignancy using the terminology of "malignancy prediction". It was used in the gynecological service of the HNGAMPSS (1994 to 1995) in patients with a diagnosis of adnexal mass, in whom laparoscopy or laparotomy was done according to negative or positive malignancy prediction. The use of laparoscopy is becoming more frequent in the diagnosis of adnexal masses although there is still concern on  whether this kind of approach is ideal for the proper oncological management. In our cases the incidence of ovarian malignancy was 0,8%, as in other reported series.